Optimizing stator/rotor pole ARC for torque and economy in electric vehicle switched reluctance motors - Saif Kh Al-Farhan; Omar Sharaf Al-Deen Yehya Al-Yozbaky (Institute of Advanced Engineering and Science, 2023)
Numerous researchers as well as the vehicle industry are paying increasing attention to the switching reluctance motor (SRM) drive. Due to its specialized qualities, SRMs are commonly used in electric vehicle applications. The stator/rotor pole arc of an 8/6 SRM is included in this study's investigation of design principles and performance improvement for poles arcs variation. Several limitations for the stator/rotor pole arc angle are derived for the design principles. These concepts are addressed in the finite element (FE) analysis of SRM topological parameters used in conventional and optimization analysis. The stator/rotor polar arc is tuned for performance using a genetic algorithm (GA) in order to maximize torque and efficiency. An ideal solution is chosen when the optimization results are represented. The proposed method can increase the maximum and average torque with (27.24%, 35.98%, 49.42%, 60.14%), (12.59%, 45.19%, 47.87%, 48.92%) for speeds [900, 1500, 2250, 3000 (rpm)] respectively, As shown by the comparison between the conventional and optimal designs. As well as the efficiency is improved (0.35%, 0.61%, 1.08%, 1.28%) for speeds [900, 1500, 2250, 3000 (rpm)] respectively.